Man is a Part of the Universe - Karapetyan, M. A.
“The universe is a living organism, because new stars are born every day,” Viktor Ambartsumian said on one occasion. The planet Earth as part of the Cosmic system is also a living system. Ancient philosophers spoke about this as they saw the world in the interactions and connections present in it. Later it was confirmed among others by J. Bruno, G. Newton, A. Shirakatsi. Currently, this idea is being confirmed by various scientific studies. In works of V.I. Vernandski, P.A. Florenski, A.L. Chijevski and Kozirev, living matter is seen as a living cosmic entity, where everything is united not only in terms of the universal connection of objects and phenomena, but also in terms of their interdependence and interconnectedness, as in the living systems.
Keywords: Physiology